Technical and Economic Description of the Research on a Measuring Device for Continuous Measurement of the Diameter and Vibration of the Workpiece during the Machining Process - Radoslav Kreheľ; Patrik Szentivanyi; Marek Kočiško; Martin Pollák (Advances in Materials Science and Engineering)
This article is devoted to the economic and technical aspects of the research on continuous noncontact measurement of the workpiece diameter during the manufacturing operation using a suitably selected and designed sensor. In order to achieve this main goal, it was necessary to meet these partial goals. We develop and describe a method of accurate continuous technical measurement of the workpiece diameter during the machining process. We propose a principle of continuous technical measurement of workpiece diameter, design a scanning method based on this principle, and verify the developed equipment on a specific case of technical measurement. At the same time, the development includes the expansion of the use for continuous noncontact measurement of workpiece vibrations. Based on test measurements, an optical sensor was selected, the analysis of which is presented in a part of the article. The introduction of this article provides a simple view of the need for continuous measurement of the workpiece diameter. The second chapter presents the current state of the problem. The third chapter is devoted to the theoretical analysis and description of practical implementations of the solution. The conclusion, as it could be expected, includes evaluation of the results.